Penanaman Pohon sebagai Edukasi Publik untuk Pelestarian Lingkungan - Shara, Yuni; Arif, Anggia; Nugroho, Ngajudin; Syahrizal, Muhammad (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Land degradation and global climate change represent serious environmental challenges that require collaborative responses from various stakeholders. This community service program aims to mitigate the impacts of environmental damage through the concrete action of tree planting while providing comprehensive public education within the Faculty of Agriculture, Universitas Islam Sumatera Utara. The implementation method utilized a participatory approach involving 62 students from Politeknik Cendana, academic staff, local communities, and partners from national and international universities. The stages of the activity began with the identification of critical land, the selection of adaptive shade and productive tree species, followed by silvicultural technique workshops and a synchronized planting action. The results of this program led to the successful planting of 1,000 tree seedlings in areas experiencing land degradation, which is projected to increase green cover and improve the micro-climate within the campus environment. Beyond the physical impact, evaluations showed a significant increase in ecological awareness and practical environmental management skills among participants. The international synergy in this activity successfully broadened participants' perspectives on global responsibility for maintaining Earth's sustainability. The success of this program reinforces that the integration of field action and public education can create an effective and sustainable environmental conservation model. The implications of this activity emphasize the importance of using digital-based monitoring technology to ensure future tree survival rates. As a successful service model, this program is expected to be replicated in other regions by strengthening multilateral collaborations between academia, the private sector, and the government to achieve broader and more massive environmental impacts.